A case of retrograde venous air embolism causing cerebral infarction following upper gastrointestinal endoscopy: A novel pathophysiological mechanism - Uldin, Hasaam H.U. (Radiol Case Rep, 2018)
The incidence of cerebral infarction following upper gastrointestinal endoscopic procedures is well described in the existing literature, with most mechanisms involving arterial travel of the embolus. We describe a case of cerebral infarction not explained by previously described mechanisms and detail the proposed occurrence of retrograde venous air embolism causing cerebral infarction following an upper gastrointestinal endoscopic procedure.